Mathematics Learning Using Japanese Multiplication Method (JAMED) Solving Multiple Problems Class III Basic Education Students - Nuritasari, Fetty; Septi Dariyatul Aini; Chairul Fajar Tafrilyanto; Sri Indriati Hasanah; Ema Surahmi (Universitas Islam Lamongan, 2024)
This research examines whether the multiplication abilities of third-grade students in Pamekasan improve before, during, and after using JAMED media for mathematics instruction. The study aims to assess the students' multiplication skills across these three stages, analyzing any observed improvements. The research employs a single subject experimental method with an A-B-A design, using action tests for data collection. The subject is a third-grade student with the initials AW. Findings show that the student’s multiplication ability was very low in the initial baseline (A1), improved to a sufficient level during the intervention (B), and reached a high level in the final baseline (A2). This indicates a significant positive impact of JAMED media on the student's multiplication skills.